Reconstruction of Infraorbital Floor using Marlex Mesh through Intraoral Vestibular Approach using Endoscope for Reduction - MN Bhaskar; UB Shabari; Shruti G Raikar; KK Suresh; P Bharathi (Journal of Pharmacy and Bioallied Sciences)
Infraorbital floor fracture is a common occurrence in cases of road traffic accidents. A variety of approaches and materials are available for the repair of such fractures. In this case series, we have discussed a conservative approach using an endoscope and the use of Marlex mesh for the repair of ZMC fractures. We have briefly discussed the importance of the selected approach and material, as well as the various advantages of using this combination.